A Study of Rayleigh Waves for Predicting Soil Carrying Capacity Using the Seismik Multi-Channel Analysis Of Surface Wave (MASW) Method - Laila, Nor; Munir, Rahmiati; Lepong, Piter (GEOSAINS KUTAI BASIN, 2023)
This research was conducted to determine subsurface lithology and soil carrying capacity in the study area by using the results of shear wave analysis using the MASW seismik method. This study used secondary seismic refraction data with three lines, where the data was collected on street Poros Samarinda-Tenggarong, East Kalimantan. Data processing is divided into two stages, namely the determination of the dispersion and inversion curves to produce shear wave velocity values. The resulting shear wave value is used to analyze the soil bearing capacity. The results of this study are that there is sandstone material (unsaturated) in the first layer and clay rock and at that location has a soil permit carrying capacity value range of 74.46-79.8 KPa with a moderate soil type class.